Moisture Sorption Behaviour and Mould Ecology of Trade Garri Sold in South Eastern Nigeria - Tochukwu Samuel; J. Obeta Ugwuanyi (International Journal of Food Science)
Garri is a creamy white or yellow starchy grit produced by roasting to gelatinization and dryness of peeled, washed, mashed, and fermented dewatered cassava roots. It is the most important product of cassava in West and Central Africa. Mean moisture content of yellow and white garri was 11.11% and 10.81% within 24 hrs of sampling from the market, increasing to 17.27% and 16.14%, respectively, following 3 months of storage at room temperature. The water activity of samples varied from initial 0.587 to 0.934 following storage. Moisture sorption isotherms, determined by static gravimetric techniques at 20° and 30°C, showed temperature dependent BET Sigmoidal type II behaviour typical of carbohydrate rich foods but modulated very slightly by the content of palm oil. Equilibrium moisture content decreased with increase in temperature at constant water activity. A total of 10 fungal species belonging to the genera Mucor, Penicillium, Cephalosporium, Aspergillus, Scopulariopsis, Rhizopus, and Paecilomyces were identified, with range increasing with water activity of samples.